THE INFLUENCE OF COMMUNICATION AND MOTIVATION ON THE WORK ENVIRONMENT IN PT PERKEBUNAN NUSANTARA IV MEDAN - Elcy Handayani Pramita; Edy Terdjo (Journal of Financial Management & Accounting, 2024)
Every company in implementing programs that are directed is always efficient to achieve the goals set. One way that works goals can be achieved by creating a comfortable work environment. The work environment is something that is around workers and can affect themselves in carrying out the tasks assigned. A poor work environment can reduce work morale and more time and do not support obtaining an efficient work system design. Many factors affect the work environment, including communication and motivation. The purpose of this study was to determine the effect of Communication and Motivation on the Work Environment of PT. Perkebunan Nusantara IV Medan both partially and simultaneously. This type of research is a quantitative descriptive method. The object of research is the employees of the Human Resources and Marketing division of PT Perkebunan Nusantara IV Medan, amounting to 56 people. The sampling technique uses a saturated sampling technique which means the population is the same as the sample. Data analysis techniques used are multiple regression analysis, t-test, F test, and the coefficient of determination test. The results showed that partially and simultaneously Communication and Motivation influenced the Work Environment of PT. Perkebunan Nusantara IV Medan. The company leadership is advised to maintain the communication process that has taken place so far, taking into account the background, character, attitude, and nature of the leadership and employees. In motivation, companies are advised to pay more attention to employee work motivation by allowing employees the opportunity to develop their skills and expertise, this can be done by providing learning opportunities for employees who have work performance.